Development of an HIV Prevention Videogame: Lessons Learned - Kimberly Hieftje; Lynn E. Fiellin; Tyra Pendergrass; Lindsay R Duncan (Serious Games Society, 2016)
The use of videogames interventions is becoming an increasingly popular and effective strategy in disease prevention and health promotion; however, few health videogame interventions have been scientifically rigorously evaluated for their efficacy. Moreover, few examples of the formative process used to develop and evaluate evidence-based health videogame interventions exist in the scientific literature. The following paper provides valuable insight into the lessons learned during the process of developing the risk reduction and HIV prevention videogame intervention for young adolescents, PlayForward: Elm City Stories.